From resilience to empowerment: The Gender and Climate Empowerment Index for climate-resilient agriculture - Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The Gender and Climate Empowerment Index for climate-resilient agriculture is based on four major measurable indicator domains—political, economic, agricultural, and social. Empowerment in relation to climate change relates to degree of vulnerability and ability to respond, recover from and adapt to climate change. In a context of growing climatic risks, appropriate technological solutions together with an empowering social environment are a prerequisite for ensuring food and livelihood security (Hariharan et al., 2020). These indicators can be used as a vital tool to understand the process of gender empowerment that can trigger the entry points to achieve gender equality, which is also an important aspect in the adoption of climate-smart agriculture practices. The Index, along with the Ghana Agriculture Profile, provides the basis for assessing empowerment in the context of gender-smart agriculture.